A kind of organic silicon potting glue for new energy vehicle battery and preparation method thereof
By using silicon micropowder and ceramic microspheres in thermally conductive silicone potting glue, silicone potting glue with a dielectric constant less than 3.0 was prepared, which solved the problem of difficult to take into account both thermal conductivity and flame retardant performance in the prior art, and achieved efficient thermal conductivity and flame retardant effects.
Patent Information
- Application Number
- CN202410790338.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2025-04-04
AI Technical Summary
While the existing thermally conductive silicone potting glue improves thermal conductivity and flame retardant properties, the dielectric constant is greater than 3.0, which cannot effectively solve problems such as signal interference, resistance and capacitor delay of electronic devices.
By combining silicon micropowder and ceramic microspheres, silicone potting glue with a dielectric constant of 2.79 was prepared, with thermal conductivity reaching 1.07W and flame retardant reaching V0, and it also meets the requirements of low viscosity, suitable density and high elongation of break.
It has achieved thermal potting adhesive with a dielectric constant below 3.0, with good thermal conductivity, flame retardant performance and fluidity, and is suitable for the application of new energy vehicle batteries.
Smart Images

Figure BDA0004899820400000061 
Figure BDA0004899820400000062 
Figure BDA0004899820400000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of organic potting adhesives, and relates to an organic silicone potting adhesive, and in particular to an organic silicone potting adhesive for new energy vehicle batteries that simultaneously meets multiple performance requirements of thermal conductivity, elongation at break, dielectric constant, breakdown voltage, flame retardancy and density, and a preparation method thereof. Background Art
[0002] New energy vehicle batteries will generate heat during use. If the heat cannot be removed in time, it is easy to damage the battery and even cause the battery to explode. In the process of preparing new energy vehicle electronics, the heat dissipation capacity of the battery is improved by using heat-dissipating potting glue. At the same time, the on-board OBC (i.e., on-board charger) is often accompanied by heat generation and electronic signal transmission when working. When transmitting some electrical signals, these electronic devices will also cause certain mutual interference. As the installation distance between them becomes closer, it will also bring many other negative effects, such as: electric field shielding effect, interference of transmission signals, resistance and capacitance delay, and increase in other energy consumption. Especially in some electronic modules with relatively high integration, these disadvantages will be more serious.
[0003] There are two common methods to reduce the dielectric constant:
[0004] One is to compound the inorganic hollow filler with silicone rubber and introduce air with low dielectric constant; CN111423842B discloses a low dielectric constant organic silicone potting glue and its preparation method, which maintains its dielectric constant below 3.0 by introducing porous materials containing air, and can maintain the stability of the porous materials. However, the porous materials not only weaken the mechanical properties of the potting glue and affect its leveling, but also have poor dispersion of the porous materials, resulting in reduced light transmittance of the potting glue.
[0005] The second is to carry out graft copolymerization on the molecular chain to introduce some groups with small polarity or large free volume; CN105153711B discloses a liquid fluorosilicone rubber for cold shrink cable accessories and its preparation method, which reduces the molecular polarizability by introducing fluorine atoms and can make the dielectric constant less than 3.0. However, hydrogen fluoride and fluorine gas will be released at high temperatures, which are highly corrosive and pollute the environment, and are not conducive to production.
[0006] The dielectric constant of conventional thermally conductive potting glue is generally between 3.0-5.0 (1MHz), which still cannot solve the problems of signal interference, resistance and capacitance delay, and increased energy consumption of electronic devices. Therefore, potting glue with a lower dielectric constant while improving thermal conductivity is the best solution to solve the existing problems. CN111423842B discloses a low dielectric constant organic silicon potting glue. The phase change potting glue can solve the problem of instability of porous materials containing air in the organic silicon system. The organic silicon potting glue is stable in storage. Although the dielectric constant is lower than 3.0 (1MHz), the thermal conductivity is not good enough.
[0007] 0.42-0.65W(m·K), which limits the application of this potting glue in the field of high heat generation chips to a certain extent.
[0008] In order to achieve high thermal conductivity and flame retardancy, existing thermally conductive silicone potting adhesives need to add a large amount of high-density thermally conductive fillers and flame retardant fillers.
[0009] For example, the Chinese invention patent application, publication number CN109439272A, publication date 2019-03-08, discloses a two-component thermally conductive flame-retardant silicone potting composition for electric vehicles, its potting and preparation method. The two-component thermally conductive flame-retardant silicone potting provided by the invention uses aluminum oxide and / or aluminum nitride as composite thermally conductive fillers to improve its thermal conductivity, and uses aluminum hydroxide to improve its flame retardant properties. However, a large amount of high-density thermally conductive fillers and flame-retardant fillers will cause the density of the thermally conductive silicone potting to be too high, increase the weight of the battery, and reduce the energy density of the battery, limiting its application in new energy vehicles. Summary of the invention
[0010] The technical problems to be solved by the present invention include: in order to achieve high thermal conductivity and flame retardant properties, the existing thermally conductive silicone potting glue has thermally conductive inorganic fillers such as aluminum hydroxide (dielectric constant of 9.86 at 1MHz), silicon powder (dielectric constant of 5.51 at 1MHz), magnesium oxide (dielectric constant of 9.65 at 1MHz), aluminum oxide (dielectric constant of 9.34 at 1MHz), zinc oxide (dielectric constant of 9.77 at 1MHz), and white carbon black (dielectric constant of 10.0 at 1MHz). At present, the potting glue with a thermal conductivity between 1-1.5W and a flame retardant of V0 basically uses one or more of aluminum hydroxide, magnesium oxide, aluminum oxide, and zinc oxide, resulting in a dielectric constant greater than 3.0 (1MHz).
[0011] According to existing patents and literature, silicone potting compounds with a dielectric constant less than 3.0 (1MHz) either do not conduct heat up to 1W or do not flame retardant to V0.
[0012] According to existing patents and literature, the density of potting glue with thermal conductivity between 1-1.5W is basically 2g / cm 3 Above, the dielectric constant is basically greater than 3.0 (1MHz).
[0013] Therefore, in order to solve the above problems, the present invention provides a silicone potting adhesive for new energy vehicle batteries and a preparation method thereof. The present invention uses silicon micropowder (dielectric constant of 5.51 at 1MHz) and ceramic microspheres (dielectric constant of 1.6 at 1MHz) to prepare a silicone potting adhesive with a dielectric constant of 2.79 (1MHz), a thermal conductivity of 1.07W, a flame retardant of 5mm to V0, a viscosity of less than 6000cp, a product that does not agglomerate for 12 months, and a density of 1.85g / cm 3 , the elongation at break is greater than 52.1%, and it also meets the requirements of thermal conductivity, elongation at break, dielectric constant, breakdown voltage, flame retardancy and density.
[0014] In order to achieve the above object, the present invention adopts the following technical solutions:
[0015] The present invention provides an organic silicon potting adhesive for new energy vehicle batteries, wherein the organic silicon potting adhesive comprises component A and / or component B;
[0016] Wherein, component A includes, by weight, 10-30 parts of vinyl-terminated polydimethylsiloxane, 1-5 parts of a cross-linking agent, 50-70 parts of a thermally conductive inorganic filler, 2-10 parts of ceramic microspheres, 0.1-0.5 parts of an inhibitor, 0.1-0.5 parts of a color paste, and 0.1-0.5 parts of a silane coupling agent;
[0017] In parts by weight, component B includes 10-30 parts of vinyl-terminated polydimethylsiloxane, 0.2-1 parts of catalyst, 50-70 parts of thermally conductive inorganic filler, 1-5 parts of ceramic microspheres, 1-5 parts of methyl silicone oil and 0.1-0.5 parts of silane coupling agent.
[0018] As a preferred embodiment of the present invention, the viscosity of the vinyl-terminated polydimethylsiloxane at 25° C. is 70-1000 mPa·s.
[0019] As a preferred embodiment of the present invention, the viscosity of the methyl silicone oil at 25° C. is 50-200 mPa·s.
[0020] As a preferred solution of the present invention, the crosslinking agent is at least one of terminal hydrogen polymethylsiloxane and pendant hydrogen polymethylsiloxane, and the viscosity of the crosslinking agent at 25° C. is 20-200 mPa·s.
[0021] As a preferred embodiment of the present invention, the inhibitor comprises an acetylene alcohol compound.
[0022] As a preferred embodiment of the present invention, the inhibitor includes at least one of ethynyl cyclohexanol, methyl butynol, 3,7,11-trimethyl dodecyn-3-ol, maleate, and fumarate.
[0023] As a preferred embodiment of the present invention, the catalyst includes at least one of a platinum catalyst and chloroplatinic acid.
[0024] As a preferred solution of the present invention, the conductive inorganic filler is silicon micropowder, and the particle size of the silicon micropowder ranges from 2 to 25 μm.
[0025] As a preferred embodiment of the present invention, the silane coupling agent includes at least one of KH550, KH560, A171 and A151.
[0026] The present invention also provides a method for preparing an organic silicon potting adhesive for a new energy vehicle battery, the preparation method comprising the following steps:
[0027] 1) Weighing part of the vinyl-terminated polydimethylsiloxane and the silane coupling agent, kneading in vacuum, adding ceramic microspheres and conductive inorganic fillers in sequence, stirring in a vacuum kneader at a negative pressure of 0.8 MPa and a temperature of 120° C. to obtain a base rubber;
[0028] 2) Preparation of component A: Dispersing the base material, the crosslinking agent, the remaining vinyl-terminated polydimethylsiloxane, the inhibitor and the color paste at high speed, stirring to obtain the above-mentioned component A;
[0029] Preparation of component B: The base material, catalyst, methyl silicone oil and the remaining vinyl-terminated polydimethylsiloxane are dispersed at high speed and stirred to obtain the above-mentioned component B.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1) The organic silicon potting glue for new energy vehicle batteries prepared by the present invention can control the dielectric constant within 3 by using silicon micropowder and ceramic microspheres through powder matching; at the same time, it meets the requirements of low viscosity, flame retardancy V0 and thermal conductivity 1.07W.
[0032] 2) The organic silicone potting glue for new energy vehicle batteries prepared by the present invention has high fluidity, good self-draining performance, and a viscosity higher than 6000cp, and cannot flow into a narrow gap of 1mm.
[0033] 3) The present invention uses silicon micropowder (dielectric constant of 5.51 at 1MHz) and ceramic microspheres (dielectric constant of 1.6 at 1MHz) to prepare an organic silicone potting compound with a dielectric constant of 2.79 (1MHz), a thermal conductivity of 1.07W, a flame retardant of 5mm to V0, a viscosity of less than 6000cp, a product that does not agglomerate for 12 months, and a density of 1.85g / cm 3, the elongation at break is greater than 52.1%, and it also meets the requirements of thermal conductivity, elongation at break, dielectric constant, breakdown voltage, flame retardancy and density. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] The present invention provides an organic silicon potting adhesive for new energy vehicle batteries, wherein the organic silicon potting adhesive comprises component A and / or component B;
[0036] Wherein, component A includes, by weight, 10-30 parts of vinyl-terminated polydimethylsiloxane, 1-5 parts of a cross-linking agent, 50-70 parts of a thermally conductive inorganic filler, 2-10 parts of ceramic microspheres, 0.1-0.5 parts of an inhibitor, 0.1-0.5 parts of a color paste, and 0.1-0.5 parts of a silane coupling agent;
[0037] In parts by weight, component B includes 10-30 parts of vinyl-terminated polydimethylsiloxane, 0.2-1 parts of catalyst, 50-70 parts of thermally conductive inorganic filler, 1-5 parts of ceramic microspheres, 1-5 parts of methyl silicone oil and 0.1-0.5 parts of silane coupling agent.
[0038] In some embodiments of the present invention, the viscosity of the vinyl-terminated polydimethylsiloxane (if it is a vinyl-terminated polydimethylsiloxane with a viscosity of 75, it is named 206-75, and so on) at 25°C is 70-1000mPa·s, and specifically, for example, it can be 75mPa·s, 100mPa·s, 200mPa·s, 500mPa·s, 1000mPa·s, etc. Selecting vinyl-terminated polydimethylsiloxane with a viscosity in the range of 70-1000mPa·s as the silane raw material in component A and component B is conducive to regulating the viscosity and fluidity of the material, reducing the difficulty of processing and the difficulty of later potting, and improving the dispersion uniformity of the filler. At the same time, the vinyl-terminated polydimethylsiloxane used in the present invention (provided by Xin'an Chemical) has a volatile matter of less than 0.5%.
[0039] In some embodiments of the present invention, the viscosity of the methyl silicone oil (if it is a methyl silicone oil with a viscosity of 50, it is named 201-50, and so on) at 25°C is 50-200mPa·s, and specifically, for example, it can be 50mPa·s, 100mPa·s, 200mPa·s, etc. Selecting methyl silicone oil with a viscosity in the range of 50-200mPa·s as the silane raw material in component B is conducive to regulating the viscosity and fluidity of the material, reducing the difficulty of processing and the difficulty of later potting, and improving the dispersion uniformity of the filler. At the same time, the methyl silicone oil used in the present invention (provided by Xin'an Chemical) has a volatile matter of less than 0.5%.
[0040] In some embodiments of the present invention, the crosslinking agent includes at least one of terminal hydrogen polymethylsiloxane (hereinafter referred to as terminal hydrogen) and side hydrogen polymethylsiloxane (hereinafter referred to as side hydrogen), which can be any one of the above substances or a combination of the two. Selecting at least one of the above substances as a crosslinking agent is beneficial to regulating the curing molding time of the silicone potting glue. The viscosity of the crosslinking agent at 25°C is 20-200mPa·s, and specific examples can be 20mPa·s, 50mPa·s, 70mPa·s, 80mPa·s, 90mPa·s, 120mPa·s, 200mPa·s, etc.
[0041] By optimizing the viscosity of the cross-linking agent, it is helpful to control the viscosity of the material to ensure the processing performance of the silicone potting glue and to facilitate the packaging of electronic components. In some embodiments of the present invention, the silicon-hydrogen ratio of the cross-linking agent is 1-1.5. The "silicon-hydrogen ratio" mentioned here refers to the atomic ratio of the silicon element and the hydrogen element in the cross-linking agent. In some specific embodiments, it can be 1, 1.1, 1.3, 1.5, etc. By optimizing the silicon-oxygen ratio of the cross-linking agent, it is helpful to control the cross-linking structure and degree of cross-linking of the siloxane to ensure the mechanical properties of the silicone potting glue after curing. At the same time, the cross-linking agent used in the present invention (provided by Xin'an Chemical) has a volatile content of less than 0.5%.
[0042] In some specific embodiments of the present invention, the inhibitor includes an acetylene alcohol compound. The acetylene alcohol compound is selected as the inhibitor, and the inhibitory effect on the reaction between the siloxane and the crosslinking agent is better. Furthermore, in some specific embodiments of the present invention, the inhibitor includes at least one of ethynyl cyclohexanol, methyl butynol, 3,7,11-trimethyl dodecyne-3-ol, maleate, and fumarate, which can be any one of the above substances, or a combination of any two or more thereof. The inhibitory effect on the reaction between the siloxane and the crosslinking agent is better when at least one of the above acetylene alcohol compounds is selected as the inhibitor.
[0043] In some embodiments of the present invention, the catalyst includes at least one of a platinum catalyst and chloroplatinic acid, which can be any one of the above substances or a combination of the two. At least one of the above substances is selected as a catalyst, which can effectively catalyze the cross-linking reaction of siloxane and the cross-linking agent after contacting with the siloxane and the cross-linking agent at the same time, thereby achieving the curing and molding of the silicone potting adhesive, and the catalytic effect is good.
[0044] In some embodiments of the present invention, the silicone potting adhesive further includes a color paste. By adding the color paste, the silicone potting adhesive can be given a certain color, so as to meet different usage requirements and improve the market competitiveness of the silicone potting adhesive. When the silicone potting adhesive is also added with a color paste, similarly, the color paste can be added to component A or component B alone, or can be added to component A and component B at the same time. Specifically, in some embodiments of the present invention, the color paste is added to component A, and the amount of the color paste added is 0.1-0.5 parts by weight. Adding the color paste to component A makes it easier to fully mix the color paste with other raw materials. Further, in some specific embodiments of the present invention, the color paste includes a black paste containing carbon powder, and the carbon powder includes insulating carbon black. The use of a black paste containing insulating carbon black is beneficial to reducing costs on the one hand, and can also ensure the insulation of the silicone potting adhesive on the other hand.
[0045] In some embodiments of the present invention, the ceramic microspheres include at least one of the product brands GS20, GS25, and GS32 produced by Maanshan Mining Institute.
[0046] In some embodiments of the present invention, the silicon micropowder (provided by Lianrui New Materials) has a particle size range of 2-25 μm, and specifically can be at least one of 2 μm, 5 μm, 10 μm, 150 μm, 20 μm, and 25 μm, and can be any one of the above substances or a combination of two. The particle size selection needs to balance the viscosity and sedimentation performance.
[0047] In some embodiments of the present invention, the silane coupling agent includes at least one of KH550, KH560, A171, and A151, which can be any one of the above substances or a combination of two of them. The function of the silane coupling agent is to react quickly with the hydroxyl group on the surface of the powder, so that the coupling agent is combined with the powder by chemical bonding to achieve the purpose of powder modification. The long-chain alkane structure exposed outside can better coat the powder, reduce the polarity of the powder surface, and then better disperse in the silicone oil to achieve the purpose of viscosity reduction. After the powder surface is wrapped by a layer of silicone oil, the powder will not be agglomerated even during long-term storage, achieving the effect of anti-sedimentation.
[0048] The present invention also provides a method for preparing an organic silicon potting adhesive for a new energy vehicle battery, the preparation method comprising the following steps:
[0049] 1) Weighing part of the vinyl-terminated polydimethylsiloxane and the silane coupling agent, kneading in vacuum, adding ceramic microspheres and conductive inorganic fillers in sequence, stirring in a vacuum kneader at a negative pressure of 0.8 MPa and a temperature of 120° C. to obtain a base rubber;
[0050] 2) Preparation of component A: Dispersing the base material, the crosslinking agent, the remaining vinyl-terminated polydimethylsiloxane, the inhibitor and the color paste at high speed, stirring to obtain the above-mentioned component A;
[0051] Preparation of component B: The base material, catalyst, methyl silicone oil and the remaining vinyl-terminated polydimethylsiloxane are dispersed at high speed and stirred to obtain the above-mentioned component B.
[0052] Example 1
[0053] The present invention tests the silane coupling agent. Except for the silane coupling agent, the other conditions are the same to prepare a base glue, wherein 5 μm silicon powder is used with 20 μm silicon powder, and the mass ratio is 1:5. The viscosity of the base glue prepared with different silane coupling agents is tested, and the results are shown in Table 1.
[0054] Table 1. Viscosity test results
[0055]
[0056] It can be seen from Table 1 that A171 was selected as the final silane coupling agent to continue the test.
[0057] Example 2
[0058] This example is the preparation of component A. The proportions of component A1 to component A7 are shown in Table 2.
[0059] Table 2. Composition of silicone potting compound component A
[0060]
[0061]
[0062] Note: The side hydrogen used in component A1-component A7 has a viscosity of 70mPa·s and a hydrogen content of 0.3%;
[0063] The terminal hydrogen used in components A1 to A7 has a viscosity of 90 mPa·s and a hydrogen content of 0.08%;
[0064] The ceramic microspheres used in component A1 to component A7 have a product grade of GS20.
[0065] Component A1 to Component A7 obtained in Example 2 were subjected to viscosity test, 1 mm narrow slit test and sedimentation test. The results are shown in Table 3.
[0066] Table 3. Test results of component A
[0067]
[0068] Note: Sedimentation test method: put 1.5Kg of component A or component B into a 1L straight-mouthed can and place it in a constant temperature and humidity room (temperature 25°C, humidity 50%).
[0069] 1mm narrow gap test method: simulate the specifications of the components to be potted, and place a 9*9 PCB board in a 10*10 square box with a height of 2mm.
[0070] It can be seen from Table 3 that the viscosity is closely related to the particle size of the powder. Theoretically, the smaller the particle size of the powder, the higher the oil absorption value will be, which will lead to higher viscosity. Therefore, component A6 uses 12.4 parts of 5μm silicon micropowder and 62 parts of 10μm silicon micropowder, and its viscosity is much greater than component A5 uses 12.4 parts of 5μm silicon micropowder and 62 parts of 20μm silicon micropowder.
[0071] Example 3
[0072] This example is the preparation of component B. The ratio of component B1 to component B3 is shown in Table 4.
[0073] Table 4. Composition of silicone potting compound component B
[0074]
[0075] The components B1 to B3 prepared in Example 3 were subjected to viscosity test, 1 mm narrow slit test and sedimentation test. The results are shown in Table 5.
[0076] Table 5. Test results of component B
[0077]
[0078] Note: Sedimentation test method: put 1.5Kg of component A or component B into a 1L straight-mouthed can and place it in a constant temperature and humidity room (temperature 25°C, humidity 50%).
[0079] 1mm narrow gap test method: simulate the specifications of the components to be potted, and place a 9*9 PCB board in a 10*10 square box with a height of 2mm.
[0080] It can be seen from Table 5 that the viscosity of component B1 is lower than 6000cp, which can meet the encapsulation requirements, and the sedimentation meets the requirements. Component B1 is then tested with component A.
[0081] Example 4
[0082] Components A1 to A7 were mixed with component B1 in a ratio of 1:1 by mass, and thermal conductivity, elongation at break, dielectric constant, breakdown voltage, flame retardancy and density were tested. The results are shown in Table 6.
[0083] Table 6. Test results
[0084]
[0085] It can be found from Table 6 that, combined with the viscosity and sedimentation of component A (see Table 4), the viscosity is lower than 6000cp and can flow smoothly into electronic components. Finally, component A5+component B1 is selected as the optimal solution of the present invention.
[0086] It can be seen that the present invention uses silicon micropowder (dielectric constant of 5.51 at 1MHz) and ceramic microspheres (dielectric constant of 1.6 at 1MHz) to prepare an organic silicone potting adhesive with a dielectric constant of 2.79 (1MHz), a thermal conductivity of 1.07W, a flame retardant of 5mm to V0, a viscosity of less than 6000cp, a product that does not agglomerate for 12 months, and a density of 1.85g / cm 3 , the elongation at break is greater than 52.1%, and it also meets the requirements of thermal conductivity, elongation at break, dielectric constant, breakdown voltage, flame retardancy and density.
[0087] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A silicone potting compound for new energy vehicle batteries, characterized in that: The organic potting compound comprises component A and / or component B; Wherein, component A includes, by weight, 10-30 parts of vinyl-terminated polydimethylsiloxane, 1-5 parts of a cross-linking agent, 50-70 parts of a thermally conductive inorganic filler, 2-10 parts of ceramic microspheres, 0.1-0.5 parts of an inhibitor, 0.1-0.5 parts of a color paste, and 0.1-0.5 parts of a silane coupling agent; In parts by weight, component B includes 10-30 parts of vinyl-terminated polydimethylsiloxane, 0.2-1 parts of catalyst, 50-70 parts of thermally conductive inorganic filler, 1-5 parts of ceramic microspheres, 1-5 parts of methyl silicone oil and 0.1-0.5 parts of silane coupling agent.
2. The organic silicone potting adhesive for new energy vehicle batteries according to claim 1, characterized in that: The viscosity of the vinyl-terminated polydimethylsiloxane at 25° C. is 70-1000 mPa·s.
3. The organic silicon potting adhesive for new energy vehicle batteries according to claim 1, characterized in that: The viscosity of the methyl silicone oil at 25° C. is 50-200 mPa·s.
4. The organic silicon potting adhesive for new energy vehicle batteries according to claim 1, characterized in that: The crosslinking agent is at least one of terminal hydrogen polymethylsiloxane and pendant hydrogen polymethylsiloxane, and the viscosity of the crosslinking agent at 25° C. is 20-200 mPa·s.
5. The organic silicon potting adhesive for new energy vehicle batteries according to claim 1, characterized in that: The inhibitors include acetylenic alcohol compounds.
6. The organic silicon potting adhesive for new energy vehicle batteries according to claim 5, characterized in that: The inhibitor includes at least one of ethynyl cyclohexanol, methyl butynol, 3,7,11-trimethyl dodecyn-3-ol, maleate, and fumarate.
7. The organic silicone potting adhesive for new energy vehicle batteries according to claim 1, characterized in that: The catalyst includes at least one of a platinum catalyst and chloroplatinic acid.
8. The organic silicon potting adhesive for new energy vehicle batteries according to claim 1, characterized in that: The conductive inorganic filler is silicon micropowder, and the particle size of the silicon micropowder ranges from 2 to 25 μm.
9. The organic silicone potting adhesive for new energy vehicle batteries according to any one of claims 1 to 8, characterized in that: The silane coupling agent includes at least one of KH550, KH560, A171 and A151.
10. A method for preparing a silicone potting compound for new energy vehicle batteries, characterized in that: The preparation method comprises the following steps: 1) Weighing part of the vinyl-terminated polydimethylsiloxane and the silane coupling agent, kneading in vacuum, adding ceramic microspheres and conductive inorganic fillers in sequence, stirring in a vacuum kneader at a negative pressure of 0.8 MPa and a temperature of 120° C. to obtain a base rubber; 2) Preparation of component A: Dispersing the base material, the crosslinking agent, the remaining vinyl-terminated polydimethylsiloxane, the inhibitor and the color paste at high speed, and stirring to obtain the component A according to any one of claims 1 to 8; Preparation of component B: Disperse the base material, catalyst, methyl silicone oil and the remaining vinyl-terminated polydimethylsiloxane at high speed and stir to obtain component B according to any one of claims 1 to 8.
Citation Information
Patent Citations
Liquid fluorosilicone rubber for cold-shrinkable cable accessories and preparation method thereof
CN105153711B
Bicomponent heat-conducting anti-flaming organosilicone pouring sealant compound for electric automobile, and pouring sealant and preparation method of bicomponent heat-conducting anti-flaming organosilicone pouring sealant compound
CN109439272A
A low dielectric constant silicone potting compound and its preparation method
CN111423842B